2022
DOI: 10.3389/fendo.2021.564344
|View full text |Cite
|
Sign up to set email alerts
|

Causes and Effects of Oocyte Retrieval Difficulties: A Retrospective Study of 10,624 Cycles

Abstract: Oocyte retrieval is a routine procedure during the application of assisted reproduction technology. However, technical difficulties experienced during oocyte retrieval and the subsequent unsatisfactory number of oocytes obtained are rarely reported. The current study included 10,624 oocyte retrieval cycles from April 2015 to June 2018, and patients were followed up until February 2019. Patients were divided into two groups depending on whether the oocyte number obtained reached the >14-mm follicle numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Furthermore, this conclusion seems to be supported by a mostly beneficial effect of sclerotherapy on the number of oocytes retrieved compared to the effect exerted by laparoscopic cystectomy. This is a favorable outcome of sclerotherapy, particularly in light of reports indicating endometriosis as a factor able to impair the process of oocyte retrieval [51]. Additionally, in the course of the research, we observed rather a lack of differences in pregnancy outcomes between groups of patients who underwent sclerotherapy and those who underwent laparoscopic cystectomy or who were untreated.…”
Section: Discussionsupporting
confidence: 47%
“…Furthermore, this conclusion seems to be supported by a mostly beneficial effect of sclerotherapy on the number of oocytes retrieved compared to the effect exerted by laparoscopic cystectomy. This is a favorable outcome of sclerotherapy, particularly in light of reports indicating endometriosis as a factor able to impair the process of oocyte retrieval [51]. Additionally, in the course of the research, we observed rather a lack of differences in pregnancy outcomes between groups of patients who underwent sclerotherapy and those who underwent laparoscopic cystectomy or who were untreated.…”
Section: Discussionsupporting
confidence: 47%
“…The microrobots, propelled by biological motors, exhibit enhanced maneuverability within the intricate reproductive anatomy, ensuring targeted oocyte retrieval while minimizing tissue trauma. These findings underscore the potential of micro/nano robots to redefine the landscape of oocyte retrieval in ART, offering novel solutions for addressing challenges associated with conventional retrieval techniques [45,49]. Through such innovations, micro/nano robots hold promise for enhancing the efficacy and patient satisfaction in ART procedures, paving the way for future advancements in reproductive medicine.…”
Section: Innovations In Oocyte Retrievalmentioning
confidence: 85%
“…Advances in micro/nano robot-assisted oocyte retrieval have attracted scientific interest and have been published in scholarly journals [31,[45][46][47]. A work by Zhau et al (2021) [46] in the Journal of Chemical Reviews demonstrates the effective use of magnetic nanorobots for precise oocyte retrieval.…”
Section: Innovations In Oocyte Retrievalmentioning
confidence: 99%
“…In our study, the progesterone level on the trigger day showed statistical significance in both the intergroup comparison and regression analysis; although the ROC analysis suggested that its predictive effect of a low ORR was not as strong as that of the E2/follicle ratio. Like estradiol, progesterone is a product secreted by ovarian granulosa cells, and the concentration of progesterone increases with the development of follicles and is positively associated with the number of oocytes [ 34 36 ]. It was found that both high and low progesterone levels in the late follicular phase resulted in reduced oocyte numbers [ 37 ].…”
Section: Discussionmentioning
confidence: 99%